Load-bearing capacity of flexural reinforced concrete members strengthened with fiber-reinforced polymer in fracture stage. (April 2018) - Slaitas, Justas; Valivonis, Juozas; Juknevičius, Linas; Šalna, Remigijus
The article examines the behavior of flexural reinforced concrete members, strengthened with fiber-reinforced polymers (FRP), under the ultimate loading conditions (in fracture stage). One of the main problems of such elements is sudden and brittle failure mode caused by FRP debonding. The method for the calculation of load-bearing capacity of the normal section of flexural reinforced concrete members, strengthened with various types of FRP, is proposed in this article. This method is based on the theory of fracture mechanics of solids. The reduction of overall member stiffness due to the slip between concrete and FRP is estimated by reducing the FRP stress according to the built-up bars theory. Such reduction allows the prediction of load-bearing capacity of strengthened members sufficiently precisely even for sudden and brittle FRP debonding failure mode. The numerical results are compared with experimental ones. In total, 55 reinforced concrete beams, strengthened with externally bonded or near surface mounted carbon fiber-reinforced polymer and glass fiber-reinforced polymer sheets, plates, strips, and rods, are analyzed in this comparison. Experimental results were collected from various scientific publications. A focus is made on the depth of the crack in critical normal section and FRP strain–stress relationship.